Правове регулювання тимчасового ввезення (вивезення) транспортних засобів - Гречаний, Дмитро Михайлович (My University, 2010)
В данной статье рассматривается специфика применения таможенного режима временного ввоза (вывоза) к отдельным видам транспортных средств. Анализируются соответствующие нормы национального и международного законодательства.

The present article provides the analyses of the specialties of the customs regime of temporary admission with respect to the different types of transport means. The proper provisions of national and international legislation are also analyzed.
Keywords: транспортні засоби; ввезення транспортних засобів; вивезення транспортних засобів; митний режим; транспортные средства; ввоз транспортных средств; вывоз транспортных средств; таможенный режим; transportation; importation of vehicles; export of vehicles; customs regime